Henry R. Brown diary - Brown, Henry R.
Diary (1862 October 6-1863 August 8) kept by Brown during his service with Company G, 15th New Hampshire Infantry, mainly in New Orleans, La., during the Civil War, with comments on the Federal occupation of the city, the training, morale, and performance of African American soldiers, and the siege of Port Hudson, La. Includes regimental casualty lists, two pencil sketches by Brown of the regiment's camp, and a hospital discharge notice.
Soldier in the Union Army.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: United States. -- Army. -- New Hampshire Infantry Regiment, 15th (1862-1863); Louisiana -- History -- Civil War, 1861-1865.; New Hampshire -- History -- Civil War, 1861-1865.; New Orleans (La.) -- History -- Civil War, 1861-1865.; Port Hudson (La.) -- History -- Siege, 1863.; United States -- History -- Civil War, 1861-1865 -- Campaigns; United States -- History -- Civil War, 1861-1865 -- Casualties; United States -- History -- Civil War, 1861-1865 -- Hospitals; United States -- History -- Civil War, 1861-1865 -- Participation, African American; United States -- History -- Civil War, 1861-1865 -- Personal narratives; Soldiers